Derivation of Brain Capillary-like Endothelial Cells from Human Pluripotent Stem Cell-Derived Endothelial Progenitor Cells - Praça, Catarina (2019)
The derivation of human brain capillary endothelial cells is of utmost importance for drug discovery programs focusing on diseases of the central nervous system. Here, we describe a two-step differentiation protocol to derive brain capillary-like endothelial cells from human pluripotent stem cells. The cells were initially differentiated into endothelial progenitor cells followed by specification into a brain capillary-like endothelial cell phenotype using a protocol that combined the induction, in a time-dependent manner, of VEGF, Wnt3a, and retinoic acid signaling pathways and the use of fibronectin as the extracellular matrix. The brain capillary-like endothelial cells displayed a permeability to lucifer yellow of 1 × 10-3 cm/min, a transendothelial electrical resistance value of 60 Ω cm2 and were able to generate a continuous monolayer of cells expressing ZO-1 and CLAUDIN-5 but moderate expression of P-glycoprotein. Further maturation of these cells required coculture with pericytes. The study presented here opens a new approach for the study of soluble and non-soluble factors in the specification of endothelial progenitor cells into brain capillary-like endothelial cells.